2010
DOI: 10.12806/v9/i1/rf1
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Attitudes and Beliefs of Incoming First-Year College Students

Abstract: Due to limited resources available for leadership development programming at colleges and universities, there is a need to better understand the leadership attitudes and beliefs of incoming first-year students in order to most efficiently develop effective leadership. The purpose of this study was to examine the leadership attitudes and beliefs of incoming first-year college students within the context of ecological leadership in order to determine if gender or ethnic differences in the leadership attitudes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 24 publications
1
28
2
Order By: Relevance
“…Furthermore, in terms of their understanding of leadership, according to the results of our study, most college leaders believe that leadership is a personal characteristic of the leader; some people, such as themselves, are leaders, while others are not. There is little empirical research on either LID or Drath's principles of leadership, however, our findings are similar to the few other empirical studies on college students and LID that have found that college students, in general, tend to have a more hierarchical than collaborative views of leadership (Fischer, Overland, & Adams, 2010;Haber, 2012) and that they view leadership as a characteristic of leaders (Shertzer & Schuh, 2004).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, in terms of their understanding of leadership, according to the results of our study, most college leaders believe that leadership is a personal characteristic of the leader; some people, such as themselves, are leaders, while others are not. There is little empirical research on either LID or Drath's principles of leadership, however, our findings are similar to the few other empirical studies on college students and LID that have found that college students, in general, tend to have a more hierarchical than collaborative views of leadership (Fischer, Overland, & Adams, 2010;Haber, 2012) and that they view leadership as a characteristic of leaders (Shertzer & Schuh, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…There is no published research investigating LID levels in college students. However, evidence suggests that students tend to have a more "leadercentric" (relating to leader identified) rather than collaborative view (relating to higher stages) of leadership (Fischer, Overland, & Adams, 2010;Haber, 2012). Komives, et al (2005) Day, et al's (2009) model and Komives, et al's (2005) arguments, in this study, we expect a linear association between stage of constructive development and stage of leader identity development.…”
Section: Constructive Development According Tomentioning
confidence: 99%
“…Gender difference findings for the leadership themes of collaborate and positive difference, with women identifying these themes more so than men, is consistent with research on students' understandings of leadership as well as their leadership practice. Women's greater emphasis on collaboration is reflective of findings from previous research that men tended to have more hierarchical thinking about leadership than women and that women demonstrated greater focus on interdependence than men (Fischer et al, 2010;Wielkiewicz, 2000). The findings from this study on gender differences for the themes of collaborate and positive difference reflect findings of women's greater self-reported behavioral measures of collaboration and citizenship as compared to men (Dugan et al, 2008).…”
Section: Discussion Of Findings By Gender Age and Racementioning
confidence: 68%
“…Cronbach's alphas for Hierarchical Thinking, Systemic Thinking, and LLS scales at T2 were .824, .831, and .902, respectively. The reliabilities of the Hierarchical Thinking and Systemic Thinking measures associated with the baseline questionnaire were .827 and .824, respectively (Fischer et al, 2010). Fisher's Z-transformation was used to test the hypothesis that the correlation between Systemic and Hierarchical Thinking would decline from T1 to T2.…”
Section: Reliability Of Measuresmentioning
confidence: 99%